Since the object is moving at a constant speed, the acceleration (\(a\)) is 0. Thus, we can simplify the motion equation:
\[ x = x_0 + v_0 t + \frac{1}{2} a t^2 \]
Substituting \(a = 0\):
\[ x = x_0 + v_0 t \]
Given:
- \(x_0 = 2 , \text{m}\) (starting position)
- \(v_0 = 15 , \text{m/s}\) (starting velocity)
- \(t = 1 , \text{s}\) (time elapsed)
Now we can plug in the values:
\[ x = 2 , \text{m} + (15 , \text{m/s} \cdot 1 , \text{s}) \] \[ x = 2 , \text{m} + 15 , \text{m} = 17 , \text{m} \]
Therefore, the final position of the object after 1 second is 17 m.